Frequency of typical complications of morphine during its intrathecal and epidural introduction in knee arthroplasty - S. V. Sokolov; V. A. Glushchenko; A. E. Mikhnin (Вестник анестезиологии и реаниматологии, 2023)
The objective was to compare the efficacy and safety of morphine in neuraxial blocks during knee arthroplasty.Materials and methods. A retrospective analysis of 60 medical histories of patients who underwent total knee arthroplasty for the period from 2017 to 2019 was performed. All patients were operated under  general anesthesia  with mechanical  ventilation in combination with epidural  or spinal analgesia with opiates. Patients of the 1st  group (n=20) after catheterization of the epidural space at the level of L1–2 were injected with a morphine solution 1% – 0.3 ml epidurally. Patients of the 2nd  group (n=20) were injected with a morphine solution 1% – 0.01 ml intrathecally at the level of L3–4. Patients of the 3rd group (n=20) underwent standard combined anesthesia:  general anesthesia  with mechanical  ventilation and epidural  analgesia at the level of L1–2  with a solution of 0.2% ropivacaine  in the form of an infusion of 6 ml/hour. All patients received infusion of 0.2% solution of ropivacaine  epidurally  6 ml/hour at the level of L1–2  in the postoperative period.The incidence of nausea, vomiting, pruritus, headache and the level of postoperative pain syndrome were assessed on a numerical rating scale 6 hours after the end of the surgery.Results. The level of pain syndrome in patients who received intrathecal and epidural analgesia with morphine was equally low, while in patients who received epidural  analgesia with ropivacaine,  the level of pain syndrome was statistically significantly  higher, which required  the additional prescription of non-steroidal anti-inflammatory drugs and/or narcotic  analgesics parenterally. The frequency  of nausea, vomiting,  pruritus and headaches was maximum in the 2nd  group, significantly lower in the 1st, while in the 3rd, pruritus did not occur.Conclusion. The use of morphine in neuraxial block in knee arthroplasty has a positive effect on the quality of anesthesia and postoperative pain relief.